Protection of Child Rights in Polygamy Family Around ASN in Asahan District Community (Analysis Study of Law No. 35 of 2014 about Child Protection) - Azwar Gunawan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
Based on Article 2 of Law Number 23 of 2002 concerning Child Protection and Law Number 35 of 2014 concerning Child Protection, that the implementation of child protection is based on Pancasila and is based on the 1945 Constitution of the Republic of Indonesia, as well as the basic principles of the Convention on the Rights of the Republic of Indonesia. children include: 1) Non-discrimination; 2) The best interests of the child; 3) Right to life, survival and development, and 4) Respect for children's opinions, it can be analyzed and concluded that everything that is urgent for children is their right that is protected by law. Positive law or also called ius constitutum is a collection of written legal principles and rules that are currently applicable and binding in general or specifically and enforced by or through the government or courts in the Indonesian state. Civil Rights, Right to Education and Maintenance, Children's Rights To get Welfare, Children's Right to Take Care of Legal Affairs, it can be analyzed and concluded that children's rights are not only schooled. But civil, welfare, even if he stumbles into a legal case, he has the right to be protected. Protection of children's rights in Law no. 35 of 2014 which states that parents are obliged and responsible for: nurturing, nurturing, educating, and protecting children, developing children according to their abilities, talents, and interests and preventing marriage at the age of children. Children are a mandate and gift from God Almighty, in whom the dignity of being fully human is attached. When polygamy is unavoidable, one of the problems that often arises is that children often become victims. Both in terms of love, education and attention. Of all the rights of children, the most urgent for children is education. Children have the right to get education from an early age as contained in the juridical basis in the body of the Constitution Chapter XIII Article 31 paragraphs 1 and 2 of 1945 which reads: every citizen has the right to receive instruction (paragraph 1) the government seeks and organize a national teaching system regulated by law.